Germination and plating efficiency of Neurospora crassa microconidia - R Kalpana; K K ADHVARYU; R MAHESHWARI (Fungal Genetics Reports, 1998)
The plating efficiency of microconidia , estimated by the number of colonies formed on a sorbose-containing medium, is commonly taken as a measure of their germinability. It has generally been low. We report that when microconidia of mcm and pe; fl strains were spread on a dialysis membrane overlying sorbose medium, their germination was greater than 80%.